Zwischen Krieg und Euthanasie Zwangssterilisationen in Wien 1940-1945 - Spring, Claudia Andrea (2009)
This publication describes in detail the preparation and realization of the forcibly sterilization of numerous women and men Vienna from 1940 to 1945. These forced sterilizations of individuals, being categorized as 'hereditary ill', were based on the 'Law for the Prevention of Genetically Diseased Offspring' (GzVeN). In Nazi Germany it took effect in January 1934, and until the outbreak of the war, when most of the court-proceedings had already ended, 300.000 women and men, had been forcibly sterilized. In January 1940 the law was implemented in the 'Ostmark', and at least 6.000 women and men had been forcibly sterilized during the war. In Vienna, the then second-largest city of the 'German Reich' 1.203 court-decisions in favour of a forcibly sterilization could be traced-back. These court-files of the 'Viennese Hereditary Health Court' (Erbgesundheitsgericht) became accessible for research only recently. The quantitative and qualitative analysis indicates three parameters for the implementation of the GzVeN in Vienna: First of all, the reduction of lawsuits to 'urgent' cases, i.e. persons of a 'particularly great danger of procreation'; secondly, the personal and structural restrictions resulting from war; and thirdly, the Nazi Euthanasia: Different from Nazi Germany the forced sterilizations had not been preceding the murder of disabled persons, but were rather implemented in the same period of time. Several doctors in Vienna were responsible for both, forced sterilizations and murder. Both judges and doctors of the 'Viennese Hereditary Health Court' were keen to contribute to the radical efforts to create the visional 'healthy national body' by fulfilling the GzVeN independent of the above mentioned parameters: they implemented a National Socialist tort-law, which included a surgical intervention with severe and lifelong psychical and physical consequences - against the will of the people who were affected. After the end of the war, the judges and doctors did not have to take any kind of responsibility for their decisions to sterilize people forcibly. This was not surprising, taking into account that the categorization of persons due to their 'value of hereditage' ('Erbwert') continued: Firstly, the then-chancellor Renner announced to pass a similar law when the GzVeN was repealed in Mai 1945; secondly, the forcibly sterilized women and men were partly acknowledged only in 1995 as victims of Nazi-persecution and fully acknowledged only 2005; and thirdly, until to the present, women, being categorized as 'disabled', are still sterilized without their knowledge and therefore without their consent. However, this bodily injury does not carry a penalty, since there is no contradiction to the so called 'good manners' ('gute Sitten'), incorporated in the criminal law.